An automated vane shear test tool for environmental monitoring with unmanned ground vehicles. (October 2020) - Olmedo, Nicolas A.; Fisseha, Bereket; Wilson, Ward; Barczyk, Martin; Zhang, Hong; Lipsett, Michael G.
Highlights: Robotic soil property measurement reduces risks & costs in challenging terrains. A robotic vane shear test tool was developed with high resolution and accuracy. Advantages over manual instrumentation are discussed with lab and field results. Sources of error, calibration, and test procedures are presented. Abstract: The present work describes the development of a novel robotic vane shear test tool for characterization of soil parameters with high precision and accuracy. The tool automates industrial standards for testing procedures. The proposed system is capable of performing high resolution torque measurements, which are then used to estimate the shear strength of the soil. The design of the instrument and its advantages over traditional manual instruments are discussed, after which error sources, calibration, and test procedures are described. The developed tool was successfully validated against high-end commercial equipment. The built unit was employed for characterizing mine waste in a laboratory setting and also deployed in the field on board an Unmanned Ground Vehicle for remote soil characterization.